2012
DOI: 10.1001/archgenpsychiatry.2011.2116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ZNF804a on Brain Structure Volumes and Symptom Severity in Individuals With Schizophrenia

Abstract: Context The single-nucleotide polymorphism rs1344706 in the gene ZNF804a has been associated with schizophrenia and with quantitative phenotypic features, including brain structure volume and the core symptoms of schizophrenia. Objective To evaluate associations of rs1344706 with brain structure and the core symptoms of schizophrenia. Design Case-control analysis of covariance. Setting University-based research hospital. Participants Volunteer sample of 335 individuals with schizophrenia spectrum disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 48 publications
2
45
2
1
Order By: Relevance
“…95 The TT subjects (n = 18) also showed reduced GMV in the angular gyrus, parahippocampal gyrus, posterior cingulate, medial orbitofrontal gyrus/gyrus rectus, left inferior frontal gyrus, right inferior temporal gyrus and right cerebellum (FDR-corrected P < 0.05). A similar study by Wassink et al 94 reported greater total (F = 3.98, P < 0.02), frontal (F = 4.95, P < 0.007) and parietal lobe (F = 3.08, P < 0.05) WMV in patients with schizophrenia (N = 335) homozygous for the T allele (n = 126), when compared to non-risk allele carriers (n = 209). The association with altered WMV across the entire brain supports the hypothesis that ZNF804A influences neural connectivity patterns across a distributed network of brain regions.…”
Section: (Ix) Neurotrophin-3 (Ntf-3/nt-3)supporting
confidence: 58%
See 1 more Smart Citation
“…95 The TT subjects (n = 18) also showed reduced GMV in the angular gyrus, parahippocampal gyrus, posterior cingulate, medial orbitofrontal gyrus/gyrus rectus, left inferior frontal gyrus, right inferior temporal gyrus and right cerebellum (FDR-corrected P < 0.05). A similar study by Wassink et al 94 reported greater total (F = 3.98, P < 0.02), frontal (F = 4.95, P < 0.007) and parietal lobe (F = 3.08, P < 0.05) WMV in patients with schizophrenia (N = 335) homozygous for the T allele (n = 126), when compared to non-risk allele carriers (n = 209). The association with altered WMV across the entire brain supports the hypothesis that ZNF804A influences neural connectivity patterns across a distributed network of brain regions.…”
Section: (Ix) Neurotrophin-3 (Ntf-3/nt-3)supporting
confidence: 58%
“…Nevertheless, structural and functional imaging studies have revealed the role of this SNP (rs1344706) in brain connectivity. 94 Healthy volunteers (N = 39) homozygous for the risk allele (T/T) (n = 18) of the ZNF804A gene rs1344706 polymorphism showed larger total WMV than carriers of the G allele (n = 21) (F (1,27) = 4.61, P < 0.041, partial eta = 0.146). 95 The TT subjects (n = 18) also showed reduced GMV in the angular gyrus, parahippocampal gyrus, posterior cingulate, medial orbitofrontal gyrus/gyrus rectus, left inferior frontal gyrus, right inferior temporal gyrus and right cerebellum (FDR-corrected P < 0.05).…”
Section: (Ix) Neurotrophin-3 (Ntf-3/nt-3)mentioning
confidence: 98%
“…In another study, schizophrenia patients who were homozygous for the TT genotype also had relatively larger GMV in the superior temporal gyrus compared with non-carriers (AC/CC). However, other studies did not replicate these findings in schizophrenia or bipolar disorder patients (Bergmann et al, 2013;Wassink et al, 2012). Several studies focused on the effects of rs1344706 variation on WM tract integrity.…”
Section: Genetic Associationmentioning
confidence: 97%
“…Following emerging interest in more derived measures of anatomy such as cortical complexity, gyrification, symmetry and thickness(34), a few studies have addressed these alterations in psychotic patients (15,(35)(36)(37)(38)(39)(40)(41)(42). Multimodal studies involved the use of MRI, eye tracking and markers of dopamine activity (25), MRI and PET(43), MRI and EEG measures (44), MRI and fMRI (40,41), MRI and genetics (32,38,45,46). Most studies focused on first-episode samples, with several MRI studies investigating the psychotic spectrum by including samples at genetic risk (28,33,37,(47)(48)(49)(50)(51)(52)(53)(54)(55) and a few studies that have investigated subjects at clinical risk for psychosis (14,31,(56)(57)(58).…”
Section: Descriptive Summary Of Findingsmentioning
confidence: 99%